2019
DOI: 10.1002/htj.21449
|View full text |Cite
|
Sign up to set email alerts
|

Numerical validation of natural convection heat transfer with horizontal rectangular fin array using straight knurling patterns on fins—correlation for Nusselt number

Abstract: Natural convection heat transfer from horizontal rectangular fin array with various knurling patterns has been studied experimentally by the present authors to investigate the effect of knurl-produced surface roughness of fin on the heat transfer rate. The parameters like knurling height from base, knurling depth, fin spacing, and supply wattage were considered for parametric study. In the present paper, numerical method (CFD) is used to simulate natural convection phenomena with knurled fins and results are v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…24 In the work, they observed that a triangular microchannel heat sink is effective with more rate of cooling per unit fin volume. In an experimental study on a straight fin with a knurled surface, Chikurde et al 25 concluded that the increasing depth and height of knurled surface negates the recirculation of natural convection currents, which results in enhanced heat dissipation. The experimental analysis done by Hameed et al 26 revealed that the efficiency of the radial heat sink with triangularedged fins, under buoyancy-driven flow, is more than that of a plain fin heat sink, which was further increased by providing holes nearer to the base of the fin.…”
Section: Introductionmentioning
confidence: 99%
“…24 In the work, they observed that a triangular microchannel heat sink is effective with more rate of cooling per unit fin volume. In an experimental study on a straight fin with a knurled surface, Chikurde et al 25 concluded that the increasing depth and height of knurled surface negates the recirculation of natural convection currents, which results in enhanced heat dissipation. The experimental analysis done by Hameed et al 26 revealed that the efficiency of the radial heat sink with triangularedged fins, under buoyancy-driven flow, is more than that of a plain fin heat sink, which was further increased by providing holes nearer to the base of the fin.…”
Section: Introductionmentioning
confidence: 99%